Communication literacy in podcast media: An inferential-ostentive discursive pragmatics perspective - Rahardi, R. Kunjana; Noviance, Kristina Marta (Universitas Ahmad Dahlan, 2025)
This study describes the pragmatic meanings of phatic communication in podcast media from a discursive pragmatic perspective based on inferential-ostentive intent. The data source comes from seven episodes of the Agak Laen podcast titled